MEMBINCANG PESANTREN SEBAGAI AKTOR PERDAMAIAN DI INDONESIA - Mustafa, M. Khoirul (Jurnal Masyarakat dan Budaya, 2015)
In recent years, pesantren is often depicted as the breeding place for terrorism and radicalism. This image emerges due to the involvement of some pesantren alumnis in violent actions such as in the Bali bombing tragedy. This image brings negative impact to pesantren while in fact this institution is rich with the texts and pratices related to peace issues. Using library research, this article discusses this problem by looking at the texts which are often used in pesantren as well as the practises that have been examplified by their alumni in the peace building activities. This article then analyzes why recently pesantren’s role in peace building activities seem blunt so that their image related to violence emerges. This article argues that this problem occur due to the modelling traditions which is currently fading within pesantren. Moreover, it is found that there is little effort to contextualize the texts interpretation within pesantren community so that they face difficulties to respond the complexity of conflict and violent cases occur in the society.